2008
DOI: 10.1074/jbc.m806315200
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Regulation of Cholesterol Levels by the Phosphatase and Hydrolase Domains of Soluble Epoxide Hydrolase

Abstract: Soluble epoxide hydrolase (sEH) is a bifunctional enzyme with two catalytic domains: a C-terminal epoxide hydrolase domain and an N-terminal phosphatase domain. Epidemiology and animal studies have attributed a variety of cardiovascular and anti-inflammatory effects to the C-terminal epoxide hydrolase domain. The recent association of sEH with cholesterol-related disorders, peroxisome proliferator-activated receptor activity, and the isoprenoid/cholesterol biosynthesis pathway additionally suggest a role of sE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 46 publications
4
60
1
Order By: Relevance
“…Previous studies show that disruption of the Ephx2 gene as well as inhibition of sEH activity by selective inhibitors result in a significant shift of the epoxy-fatty acid to diol ratio (18,22,23). Physiological and biochemical insulin signaling data support our conclusion that decreasing sEH and thus increasing plasma levels of EETs provide beneficial effects on glucose regulation possibly through modulating insulin sensitivity.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous studies show that disruption of the Ephx2 gene as well as inhibition of sEH activity by selective inhibitors result in a significant shift of the epoxy-fatty acid to diol ratio (18,22,23). Physiological and biochemical insulin signaling data support our conclusion that decreasing sEH and thus increasing plasma levels of EETs provide beneficial effects on glucose regulation possibly through modulating insulin sensitivity.…”
Section: Discussionsupporting
confidence: 85%
“…Because this sEHI has high bioavailability and a long half life (21), the high doses used resulted in high blood and tissue levels of TUPS generating a chemical knockout. Previous studies showed that plasma levels of EETs are elevated in the presence of TUPS and in KO mice (22). In spite of the high doses of TUPS, no adverse effects were seen in the pathological analysis of various organs.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Consistent with plasma cholesterol concentrations, liver expression of b-hydroxy-b-methylglutaryl coenzyme A reductase, an enzyme integral for the production of cholesterol, was found to be ;50% lower in sEH knockout male mice. Furthermore, the sEHI AR9276 significantly lowered cholesterol in an animal model of abdominal aortic aneurysm (29).…”
Section: Lipid Metabolismmentioning
confidence: 94%